A review of research progress on factors influencing death in COVID-19 patients - Wenyuan ZHENG; Jianxiong HU; Jing ZHAO; Zuhua RONG; Guanhao HE; Xing LI; Jianpeng XIAO; Wenjun MA (Zhongguo gonggong weisheng)
Coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), is an acute respiratory infection. The majority of infected individuals present with either asymptomatic or mild symptoms, such as dry throat, sore throat, cough, and fever. However, a small percentage of patients may progress to severe illness and even mortality. This study conducted a comprehensive review of relevant reports and literature on COVID-19-related deaths published nationally and internationally between January 1, 2020 and December 31, 2022. The factors influencing death in COVID-19 patients are summarized from five perspectives: clinical manifestations, individual characteristics, socio-cultural influences, governmental interventions, and viral strains. The objective is to provide scientific evidence for the prevention of adverse outcomes in COVID-19 patients and theoretical support for the enhancement of treatment protocols.